Implementasi Teknologi Blockchain Dalam Akuntansi Digital UMKM: Systematic Literature Review - Nurul Hidayah, Laily; Dista Amalia Arifah (Jurnal Ilmiah Raflesia Akuntansi, 2025)
Abstract: This study discusses the implementation of blockchain technology in digital accounting for Micro, Small, and Medium Enterprises (MSMEs). MSMEs have a strategic role in the Indonesian economy and contribute significantly to Gross Domestic Product (GDP). A systematic literature review is used to obtain a comprehensive picture of the potential and challenges of blockchain technology in the context of digital accounting. This study collected and analyzed 22 selected relevant articles, using a research protocol that included inclusion and exclusion criteria. The Systematic Literature Review (SLR) method was used in this study, which included the planning, implementation, and reporting stages systematically to ensure data quality and relevance. The results of this study indicate that blockchain technology can improve efficiency, effectiveness, transparency, and security in MSME financial management. Blockchain technology can also support better decision-making and reduce operational costs. However, this study has limitations, especially related to the geographical scope that only focuses on Indonesian MSMEs and the availability of literature is still limited. Therefore, suggestions for future research emphasize the importance of broader empirical studies, involving various types of MSMEs and different geographical contexts. This suggestion also emphasizes the importance of analyzing the readiness of technological infrastructure and specific education and training needs for MSME actors. Blockchain technology has significant potential to revolutionize digital accounting in MSMEs. However, the implementation of this technology requires a holistic approach that considers technological, social, and policy aspects to achieve optimal success. Keywords: Blockchain, Digital Accounting, MSMEs, Technology Implementation, Financial Efficiency.